Meta-analysis as an emerging trend to scrutinize the effectiveness of L2 pragmatics instruction - Shakki, Farzaneh (Frontiers in Psychology, 2022)
How efficient is instruction in pragmatics? We have attempted to answer this question through meta-analyses. Considering the plethora of studies conducted in L2 pragmatics instruction, it is still challenging for researchers to keep up with the literature, so aggregating the findings across multiple studies and comparing their results systematically in various dimensions can be pivotal to deciding whether this kind of research is effective or not. This review paper delineates the previous meta-analyses and reviews conducted in the field of instructed second language pragmatics in EFL/ESL context to explore the importance of conducting meta-analyses and to recommend some suggestions and pedagogical implications for further studies.